Elaboración de una herramienta práctica, para el cálculo de los costos en el sector panificador de la ciudad de Duitama, con estudio particular en la Panadería Chano's (2020)
The purpose of the degree work is to provide a practical instrument, this is aimed at the bakery sector, which allows to obtain in a practical and timely manner the production costs incurred in each process, improving the sector's income.